Effect of the vancomycin minimum inhibitory concentration on clinical outcomes in patients with methicillin-susceptible Staphylococcus aureus bacteraemia: a systematic review and meta-analysis. Issue 1 (15th January 2021) - Shi, Changcheng; Ye, Jian; Xu, Renjie; Jin, Weizhong; Xu, Shuang; Teng, Fei; Lin, Nengming
Abstract : Objective: The use of the vancomycin minimum inhibitory concentration (MIC) as a prognostic predictor in patients with methicillin-susceptible Staphylococcus aureus (MSSA) has been debated in the last decade. We performed a systematic review and meta-analysis to investigate whether an elevated vancomycin MIC is associated with a worse prognosis for patients with MSSA bacteraemia. Design: Systematic review and meta-analysis. Data sources: PubMed, Embase and the Cochrane Library were searched from inception to December 2019. Eligibility criteria: Randomised controlled trials or observational studies were considered eligible if they provided clinical outcomes of patients with MSSA bacteraemia, stratified by vancomycin MIC. Data synthesis: Primary outcome was mortality. Secondary outcomes included septic thrombophlebitis, persistent bacteraemia and complicated bacteraemia. Pooled ORs and 95% CIs were calculated. Subgroup analyses included the susceptibility testing method. Results: Fifteen observational studies were included. Bacteraemia due to MSSA isolates with high vancomycin MICs was associated with higher mortality than isolates with low MICs (OR 1.44; 95% CI 1.12 to 1.84; I 2 =40.3%). Additionally, significantly greater septic thrombophlebitis (OR 3.16; 95% CI 1.11 to 9.00; I 2 =58.6%) and a trend towards more persistent bacteraemia (OR 1.79; 95% CI 0.97 to 3.31; I 2 =0%) were observed in patients with high vancomycin MICs than in patients with low MICs. Differences in complicated bacteraemia were not significant. Similar findings were obtained in subgroup analyses using Etest. However, significant differences in outcomes were not observed between the high and low vancomycin MICs detected using broth microdilution. Conclusion: The available data suggest an association between elevated vancomycin MICs detected using Etest and adverse clinical outcomes for patients with MSSA bacteraemia. Future studies should validate these findings and explore the potential mechanisms. PROSPERO registration number: CRD42018090547.